Associations of cannabis and cigarette use with psychotic experiences at age 18: findings from the Avon Longitudinal Study of Parents and Children. Issue 16 (December 2014) - Gage, S. H.; Hickman, M.; Heron, J.; Munafò, M. R.; Lewis, G.; Macleod, J.; Zammit, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background. A clearer understanding of the basis for the association between cannabis use and psychotic experiences (PEs) is required. Our aim was to examine the extent to which associations between cannabis and cigarette use and PEs are due to confounding. Method. A cohort study of 1756 adolescents with data on cannabis use, cigarette use and PEs. Results. Cannabis use and cigarette use at age 16 were both associated, to a similar degree, with PEs at age 18 [odds ratio (OR) 1.48, 95% confidence interval (CI) 1.18–1.86 for cannabis and OR 1.61, 95% CI 1.31–1.98 for cigarettes]. Adjustment for cigarette smoking frequency (OR 1.27, 95% CI 0.91–1.76) or other illicit drug use (OR 1.25, 95% CI 0.91–1.73) substantially attenuated the relationship between cannabis and PEs. The attenuation was to a lesser degree when cannabis use was adjusted for in the cigarette PE association (OR 1.42, 95% CI 1.05–1.92). However, almost all of the participants used cannabis with tobacco, including those who classed themselves as non-cigarette smokers. Conclusions. Teasing out the effects of cannabis from tobacco is highly complex and may not have been dealt with adequately in studies to date, including this one. Complementary methods are required to robustly examine the independent effects of cannabis, tobacco and other illicit drugs on PEs.